2005 yılına doğru Türkiye ve Avrupa birliği muhasebe standartlarının uluslararası finansal raporlama standartlarına entegrasyonu ve bir yaklaşım - (:unkn) unknown (My University, 2004)
Türkiye'nin 2004 Yılının sonunda Avrupa Birliği ile görüşmeler için masaya oturmasına ilişkin yüksek bir beklentisi vardır. Bu nedenle bu incelemede Türk ve Avrupa Birliği Muhasebe Standartlarının karşılaştırılması amaçlanmıştır. Türkiye'de Muhasebe Standartları, ilgili kurumlar tarafından geliştirilmektedir. 01.01.2005 tarihinden sonra Sermaye Piyasasına kayıtlı olan şirketler, Uluslararası Finansal Raporlama Standartlarını uygulayacaklardır. Avrupa Birliği'ne ilişkin şirketlerde 2005 yılının sonundan itibaren UFRS'nı uygulamak zorundadırlar. Bu işlem Yönergeleri dünya çapında uyumlaştırılmış standartlarla aynı çizgiye getirecektir.

There is highly expectation in the Goverment that Turkey will seat to the table for the negotiations with the European Union by the end of year 2004.Therefore this study aimed is to compare of Turkish and European Union Accounting Standards. The Commission establishes the standardisation and harmonization of corporate and accounting rules through the issuance of Directives and Regulations. Turkish Accounting Standards have beeen developing by the related instutions in Turkey, which will start for using Intenational Financial Reporting Standards after the year of 01.01.2005 by the listed companies in the Stock Market. The European Union's companies also must follow international Financial Reporting Standards by the end of year 2005 which will bring the Directives into line with coordinated worldwide accounting practices harmonized standards.
Towards to the year of 2005 integration of Turkish and European union accounting standards to the international financial reporting standards and an approach
Keywords: İşletme Finans; İktisat; Uluslararası İlişkiler; Hukuk; İşletme; Siyasi Bilimler